PROGRESSIVE RATE MOTOR VEHICLE TAXES AND TRANSFER OF NAME DUTY ON REGIONAL ORIGINAL INCOME DURING COVID 19 PANDEMIC AT UPT. SAMSAT MEDAN SELATAN - Pandapotan Ritonga; Dwi Hidayah Aritonang (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the progressive rate of motor vehicle tax on local revenue during the COVID-19 pandemic at UPT. South Medan Samsat. To find out the transfer fee for local original income during the COVID-19 pandemic at UPT. South Medan Samsat. To find out the progressive rate motor vehicle tax and transfer fees on local revenue at UPT. Samsat, South Medan. This research uses associative research. The population and sample in this study were employees at the UPT office. South Medan Samsat as many as 100 people. The data collection technique used in this study was distributing questionnaires to employees at UPT. South Medan Samsat. The data analysis technique used in this study is quantitative data analysis using multiple regression, classical assumption test, hypothesis testing, coefficient of determination, testing in this study was carried out using SPSS version 22.0 software. The results of this study indicate that partially Progressive Tariff Motor Vehicle Tax has an effect on Regional Original Income at UPT.Samsat, South Medan. The Transfer Fee for Motorized Vehicles has an effect on Regional Original Income at UPT.Samsat, South Medan. And simultaneously the Progressive Tariff Motor Vehicle Tax and Transfer Fees have an effect on Regional Original Income at UPT.Samsat, South MedanKeywords: Progressive Tariff Motor Vehicle Tax, Transfer Fee, Local Revenue.